Star-polymer multidentate-cross-linking strategy for superior operational stability of inverted perovskite solar cells at high efficiency. Issue 10 (26th August 2021) - Cao, Qi; Yang, Jiabao; Wang, Tong; Li, Yuke; Pu, Xingyu; Zhao, Junsong; Zhang, Yixin; Zhou, Hui; Li, Xiaoqiang; Li, Xuanhua
Abstract : A multidentate-cross-linking strategy using adequate functional groups in star-polymer to directly chelate perovskite materials in multiple directions achieves superior device stability at high efficiency. Abstract : Metal halide perovskites have attracted great attention and are rapidly developing mainly due to their excellent optoelectronic properties. Currently, the efficiency of inverted (p–i–n) PSCs is around 23%, which is catching up with that of the regular structured devices. Short-term and low-efficiency operational stability are the main obstacles to the commercialization of PSCs. Although many modified materials have been proven to effectively enhance device performance, they do not satisfy operational stability at high efficiency. Here, we propose a multidentate-cross-linking strategy, which uses multi-branched and adequate chemical anchor sites in three-dimensional star-polymer to directly chelate perovskite materials in multiple directions, thereby regulating the morphology of perovskite, passivating defects at surface/GBs, inhibiting the non-radiative recombination, and improving the stability of the device. As a result, the modified PSC achieves a 22.74% efficiency, which is one of the highest values reported for the inverted PSCs. Meanwhile, the encapsulated modified device exhibits significant advancement of operational stability with 93% of the initial efficiency (∼22.00%) under maximum power point tracking at 45 °C for 1000 h, and an estimated T80 (time to retain 80% of the initial efficiency) lasted nearly 4000 h. The three-dimensional star-polymer multidentate-cross-linking strategy has proved to be a new direction for realizing commercial applications of PSCs with excellent operational stability for high-efficiency devices.